Evaluation of the degree of technological innovation in micro and small Engineering companies of Crajubar (Research, Society and Development, 2020)
The construction sector has a large share of the Brazilian GDP and labor market, and with the unfavorable economic scenario, the importance of public policies of science, technology and innovation by universities and companies increases. Most companies in the sector are micro and small with low innovative level. In this context, the present work aims to measure the degree of innovation of civil construction offices in the conurbate of Crajubar, which includes the municipalities of Crato, Juazeiro do Norte de Barbalha. The research characterized as exploratory and qualitative, sought to know and qualify the offices of the sub-region and measure their degree of innovation. The innovation survey was used, based on the model proposed by Sawhney, Wolcott and Arroniz (2006), the Innovation Radar that uses twelve dimensions, areas where the company can insert innovations and detect possible points of improvement, this tool was complemented by Bachmann and Destefani (2008) with the innovative ambience dimension. The results show an average degree of innovation of 2.99, indicating an incipient and uninnovative stage of innovation. Offices tend to apply innovations in certain dimensions, needing to be expanded in the system more broadly, remaining competitive in the market.